Differentiation of Lymphoma versus Sarcoidosis in the Setting of Mediastinal - Hilar Lymphadenopathy: Assessment with Diffusion-Weighted MR Imaging - Gümüşta, S.; İnan, N.; Akansel, G.; Başyi̇ği̇t, İ; Çi̇ftçi̇, E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Objectives: To determine the performance of diffusion-weighted magnetic resonance imaging in differentiating lymphoma from sarcoidosis in mediastinal-hilar lymphadenopathy. Materials and Methods: Fortyfour mediastinal-hilar lymphadenopathy were examined in 27 patients with T1- and T2-weighted conventional images. Then, two diffusion-weighted images were obtained with b = 0 and 1000 s/mm2 values and apparent diffusion coefficients (ADCs) were calculated. The statistical significance of differences between measurements was tested using the Student-t test. Results: The ADC value in the lymphoma group was lower than in the sarcoidosis group, and the difference was statistically significant (p < 0.001). By using the cut-off value of 1.266 x 10-3mm2/s, ADC had a sensitivity of 100%, specificity of 81%, positive predictive value of 100%, and negative predictive value of 77% for the differentiation of lymphoma and sarcoidosis.With the cut-off value of 1,97 x 10-3mm2/s, ADC had a sensitivity of 50%, specificity of 99.4%, positive predictive value of 68%, and negative predictive value of 91%. Conclusions: Diffusion-weighted imaging may be useful besides other modalities in differentiating lymphoma from sarcoidosis in mediastinal-hilar lymphadenopathy.